Climate Changes, Shifting Ranges: Climate change effects on wildlife in the Florida Everglades and Keys: WEC383/UW428, 4/2017 - Perez, Larry; Watling, James I.; Bucklin, David; Basille, Mathieu; Mazzotti, Frank J.; Romañach, Stephanie S.; Brandt, Laura A. (EDIS, 2017)
Where do the animals go when the sea rises? Learn the probable futures of Florida panthers and other south Florida wildlife in this 5-page fact sheet. Written by Larry Perez, James I. Watling, David Bucklin, Mathieu Basille, Frank J. Mazzotti, Stephanie Romañach, and Laura Brandt and published by the UF Department of Wildlife Ecology and Conservation, it explains how a changing climate could impact wild animals.edis.ifas.ufl.edu/uw428